4',6-Dihydroxy-4-methoxyisoaurone Inhibits the HIF-1α Pathway Through Inhibition of Akt/mTOR/p70S6K/4E-BP1 Phosphorylation - Chunliu Mi; Juan Ma; Hui Shi; Jing Li; Fei Wang; Jung Joon Lee; Xuejun Jin (Elsevier, 2014)
Abstract.: 4',6-Dihydroxy-4-methoxyisoaurone (ISOA) is an isoaurone compound isolated from Trichosanthes kirilowii seeds, which was identified as an inhibitor of tumor growth. However, the mechanism by which ISOA inhibits hypoxia-inducible factor-1 (HIF-1)-mediated tumor growth is not fully understood. We here demonstrated the effect of ISOA on HIF-1 activation. ISOA showed a potent inhibitory activity against HIF-1 activation induced by hypoxia in various human cancer cell lines. This compound markedly decreased the hypoxia-induced accumulation of HIF-1α protein dose-dependently, whereas it did not affect the expressions of HIF-1β and topoisomerase-I (Topo-I). Further analysis revealed that the suppression of HIF-1α accumulation by ISOA was closely correlated with strong dephosphorylation of Akt, mammalian target of rapamycin (mTOR), and its effectors ribosomal protein S6 kinase (p70S6K) and eukaryotic initiation factor 4E-binding protein-1 (4E-BP1), a pathway known to regulate HIF-1α expression at the translational level. Furthermore, ISOA prevented hypoxia-induced expression of HIF-1 target genes and suppresses the invasiveness of tumor cells. Taken together, our results suggested that ISOA is an effective inhibitor of HIF-1 through targeting Akt/mTOR/p70S6K/4E-BP1 pathway, thereby, providing new perspectives into the mechanism of its anticancer activity. Keywords:: 4',6-dihydroxy-4-methoxyisoaurone, HIF-1α, translation, antitumor